LEGAL ANALYSIS OF THE PUBLIC PROSECUTOR'S ERRORS IN MAKING AMENDMENTS TO THE CHARGES - IMAM LAHAYA, ACHMAD; MAYASARI MUIN, AUDYNA; INDRAWATI, DARA (Awang Long Law Review, 2020)
Amendments in charges are not recognized in the Criminal Procedure Code (KUHAP). There is no mechanism for changing the charges, the Criminal Procedure Code only allows the Prosecutor to change the indictment, in practice it was found that the Public Prosecutor in his response (replik) corrected the indictment which he read out regarding errors regarding evidence where there is one piece of evidence that is not related to the case so that the Public Prosecutor correcting by reflecting/crossing out because it is not included in the evidence receipt at the time of transfer of this case to the Court. This paper aims to analyze the arrangements for the Public Prosecutor's claim letter based on statutory regulations. The result of the research shows that the letter of demands for the Public Prosecutor is determined in the Criminal Procedure Code and the Law on the Prosecution, read out after the examination process has been completed. The examination referred to is the examination of valid evidence in criminal law, namely witness statements, expert statements, letters, instructions and statements of the Defendant, as well as examination of evidence. The indictment contains the charges for the sentence against the Defendant, the indictment is based on the indictment which contains a description of the incident of the criminal act and the Article that is suspected to be proven in the process of examining the evidence.